The Role of Project-Based Learning in Enhancing Elementary School Students' Creativity: A Literature Review - Samsidar Samsidar (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of Project-Based Learning (PjBL) in enhancing creativity in elementary school students through a literature review. The approach used was a qualitative literature review method, involving the analysis of various relevant studies published in the last five years (2019–2024). Data were collected from scientific articles, journals, and proceedings obtained through academic databases such as Google Scholar and ResearchGate with keywords related to PjBL and elementary school students' creativity. The results of the literature synthesis indicate that PjBL can encourage the development of student creativity through active involvement in problem-solving, collaborative work, and the creation of authentic products. This model has also been shown to enhance dimensions of creativity, namely fluency of ideas, flexibility of thinking, originality, and elaboration. The success of PjBL is influenced by several factors, such as the role of the teacher as a facilitator, the use of real-world contexts, and process- and product-based assessments. Despite implementation challenges, utilizing local resources and structured project planning can be practical solutions. Thus, PjBL is recommended as an innovative learning strategy to support the development of 21st century skills, especially creativity, at the elementary school level.